Towards Inclusive Education: A Case Study of IGNOU - S. V. S. Chaudhary (Commonwealth of Learning, 2016)
India catered to about 20 per cent of the youth in the age group 17 to 24 years. However, to achieve the threshold level of about 30 per cent by 2020, and address concerns which perpetuate inequalities in opportunities to higher education, Government of India (GoI) formulated positive discrimination policies. Establishment of Indira Gandhi National Open University (IGNOU) was one such positive step in this direction. Since 1987, IGNOU has been striving for inclusive education and reach all groups till the last mile. As a result of its dedicated efforts, at the end of 2012, it had reached 639 out of 659 districts in the country, including those in the red corridor (infested by Naxalite and Maoist extremists) passing through States of Andhra Pradesh, Chhattisgarh, Jharkhand, Maharashtra, Odisha, and West Bengal. IGNOU has been successfully imparting education and training to socially, economically, physically and/or geographically disadvantaged, in addition to women, minorities and jail inmates. Our results show that participation of rural women is particularly encouraging in all programmes but the dropout rate of these groups is rather high and success rate comparatively low.